Broadband SiN Interleaver With a Ring Assisted MZI Using a Tapered MMI Coupler - Laaya Sabri; Ranim El Ahdab; Frederic Nabki; Michael Menard (IEEE Photonics Journal, 2024)
We present an interleaver using a Ring-Assisted Mach-Zehnder Interferometer (MZI) where the ring is coupled to one arm of the MZI through a linearly tapered multimode interferometer (MMI), harnessing the advantages of both the MMI coupler and ring assisted MZI to optimize performance. The tapered MMI coupler extends the operational bandwidth of the interleaver over more than 85 nm due to its wavelength-insensitive response and precisely tailored coupling ratio. Furthermore, it removes the need for thermal tuning of the coupling region, which reduces the power consumption and overall size of the device. The experimental performance of a silicon nitride based interleaver with a channel spacing of 0.8 nm in L-band is reported. The device shows a crosstalk level below 15 dB over a wavelength range of 85 nm.